E.D.E.N. Southworth : recovering a nineteenth-century popular novelist - Homestead, Melissa J., 1963-; Washington, Pam (University of Tennessee Press, 2012)
The prolific nineteenth-century writer E.D.E.N. Southworth enjoyed enormous public success in her day - she published nearly fifty novels during her career - but that very popularity, combined with her gender, led to her almost complete neglect by the critical establishment before the emergence of academic feminism. Even now, most scholarship on Southworth focuses on her most famous novel, The Hidden Hand. However, this new book - the first since the 1930s devoted entirely to Southworth - shows the depth of her career beyond that publication and reassesses her place in American literature. Editors Melissa Homestead and Pamela Washington have gathered twelve original essays from both established and emerging scholars that set a new agenda for the study of E.D.E.N. Southworth's works. Following an introduction by the editors, these articles are divided into four thematic clusters. The first, 'Serial Southworth, ' treats her fiction in periodical publication contexts. 'Southworth's Genres, ' the second grouping, considers her use of a range of genres beyond the sentimental novel and the domestic novel. In the third part, 'Intertextual Southworth, ' the essays present intensive case studies of Southworth's engagement with literary traditions such as Greek and Restoration drama and with her contemporaries such as Harriet Beecher Stowe and French novelist George Sand. Southworth's focus on social issues and reform figures prominently throughout the volume, but the pieces in the fourth section, 'Southworth, Marriage, and the Law, ' present a sustained inquiry into the ways in which marriage law and the status of women in the nineteenth century engaged her literary imagination. The collection concludes with the first chronological bibliography of Southworth's fiction organized by serialization date rather than book publication. For the first time, scholars will be able to trace the publication history of each novel and will be able to access citations for lesser-known and previously unknown works. With its fresh approach, this volume will be of great value to students and scholars of American literature, women's studies, and popular culture studies. MELISSA J. HOMESTEAD is the Susan J. Rosowski Associate Professor of English at the University of Nebraska - Lincoln. Her book American Women Authors and Literary Property, 1822-1869 includes Southworth, and her articles on American women's writing have been published in a variety of academic journals. PAMELA T. WASHINGTON is Professor of English and former dean of the College of Liberal Arts at the University of Central Oklahoma. She is the co-author of Fresh Takes: Explorations in Reading and Writing: A Freshman Composition Text.